Hydrogen and Major Industrial Accidents - Hydrogen as a Sustainable Energy Solution: Balancing Potential with Safety Challenges - Atef Mahmoud; Vojtech Jankuj; Ales Bernatik (Chemical Engineering Transactions)
The urgent need for a shift to cleaner energy sources arose from global environmental concerns, particularly depletion of fossil fuels and their harmful effects on air quality and climate change. Being environmentally friendly, hydrogen is an appealing candidate for GHG-free energy generation and thus forms a key pillar of sustainable energy strategies. As governments, especially in the European Union, set far-reaching targets for climate neutrality, hydrogen is finding increasing applications in many sectors, ranging from industries to power generation and transportation. Hydrogen's versatility as energy carriers has opened a floodgate for research and development activities with the aim of improving its production, storage, and distribution processes. On the other side of the coin, hydrogen presents safety hazards related to its combustibility and volatility, thus requiring strict control and surveillance protocols to underpin advanced safety technology. The paper gives a comprehensive treatment of hydrogen's potential as a clean energy source and talks about its contribution to the global decarbonization agenda while analyzing safety incidents of the past with the lessons that can be highlighted. In addition, emphasis is placed on ensuring that strong safety measures—such as risk assessment, leak detection systems, and necessary regulations—are in effect to secure any dangers that hydrogen may pose. Through overcoming these hurdles, however, hydrogen can play an important role in achieving a sustainable and secure energy future.